Prinsip-prinsip Islam Tentang Ekonomi: Islamic Principles Regarding Economics - Puan Maharani Ariel Palasthree Ulil Amri; Nancy Eka Setiawati; Zaandya Fauziah Nur Hidayat; Amanda Miftahul Janah; Awalia Desvia Rahma Agzelianti; Mahandika Yuda Maruly (Litera Academica Publishing, 2025)
This research aims to find out and explore Islamic principles in the concept of Islamic Economics, as well as their application as a solution to various global economic challenges, such as social inequality, resource exploitation and economic instability. This research is a type of qualitative research using a literature study method. The research results show that Islamic Economics as an economic science based on Islamic teachings sourced from the Al-Qur'an and al-Sunnah, Ijma' (ulema agreement), and qiyās (analogy) formulates an economic system that is different from other Islamic economic systems. other systems. This is because Islamic Economics has its roots in sharia which is a source and guide for every Muslim and his activities. Islam has sharia goals which refer to human interests in achieving prosperity and a better life, and also has very important values ​​for brotherhood and socio-economic justice. The principles of Islamic Economics are based on five universal values ​​which include tauhid (faith), 'adl (justice), nubuwwah (prophecy), khilafah (government), and ma'ad (results). The results of this study confirm that the application of Islamic principles in Islamic economics has an important role in maintaining a balance between economic growth and social justice. This study produces findings that have the potential to become a basis for academic policy makers and practitioners to design more effective strategies in realizing an Islamic economy based on Islamic principles.